Laying down the sword : why we can't ignore the Bible's violent verses - Jenkins, Philip, 1952- (New York : HarperOne, 2011)
Philip Jenkins identifies the "holy amnesia" that, while allowing scriptural religions to grow and adapt, has demanded a nearly wholesale suppression of the Bible's most aggressive passages, leaving them dangerously dormant for extremists to revive in times of conflict. Jenkins lays bare the whole Bible, without compromise or apology, and equips us with tools for reading even the most unsettling texts, from the slaughter of the Canaanites to the alarming rhetoric of the book of Revelation--From publisher description.
Scripture as problem. Everything that breathes -- Truth and history -- Words of the sword -- The inheritance. Sons of Joshua -- Warrant for genocide -- Amalekite nightmares -- Truth and reconciliation. Judging God -- Coming to terms -- Historians and prophets -- Preaching the unpreachable -- Scripture alone?
Includes bibliographical references and index.
Keywords: Bible -- Criticism, interpretation, etc; Peace -- Religious aspects -- Christianity; Apologetics